The Asset Inventory Maintenance System Using the Genetic Algorithm Method at the National University: Asset Inventory Maintenance System Using the Genetic Algorithm Method at the National University - Iqbal Fajar Afrian; Moh. Iwan Wahyuddin; Novi Dian Natasha (Institute of Computer Science (IOCS), 2020)
Scheduling the maintenance of asset inventory is very important in increasing effectiveness and work efficiency. National University has fixed assets as supporting lectures such as computers, air conditioners, printers, projectors, and others. However, the asset inventory management at the National University has not yet reached effectiveness and good efficiency, the National University does not yet have a special asset database to facilitate scheduling and improvement in maintaining asset inventory. This makes it difficult to track down asset damage. This problem often makes it difficult for asset managers at the National University to know the condition of the assets, whether damaged or lost. That makes asset management not good. Therefore, a system that can run an asset management business process is neat and structured so that asset managers can easily manage maintenance maintenance and repair assets. The design process uses the Genetic Algorithm method. it starts with identifying the asset management system at the National University and creating a proposed new system. From the design stage, a website-based information system is produced to manage the scheduling and repair of assets at the National University. it starts with identifying the asset management system at the National University and creating a proposed new system. From the design stage, a website-based information system is produced to manage the scheduling and repair of assets at the National University. it starts with identifying the asset management system at the National University and creating a proposed new system. From the design stage, a website-based information system is produced to manage the scheduling and repair of assets at the National University